Historical and current distribution of segetal weed Lolium temulentum L. in Slovakia - Eliáš jun., Pavol; Hajnalová, Mária; Eliášová, Mariana (Hacquetia, 2015)
The past and present distribution of a rare segetal weed darnel ryegrass (Lolium temulentum) in Slovakia is presented. The study is based on revision of herbarium specimens from 12 herbaria and a field survey carried out during 2005–2009. Altogether, 95 localities of this species were recorded in Slovakia. Prior to 1950 it was a relatively abundant taxon recorded and confirmed at 75 localities throughout the country, but then it began to vanish. Only 20 localities were recorded between 1950 and 1990, and in 1999 it was evaluated as extinct from Flora of Slovakia. However, since 2005 new occurrences were discovered in northern Slovakia (Orava and Pieniny regions), and its status had been changed. Results of the study are summarised in the map of historical and actual species distribution.